Myopia Progression in Low Birth Weight Infants: A Narrative Review - Amir Ahmadzadeh Amiri; Majid Reza Sheikhrezaee; Ahmad Ahmadzadeh Amiri (Mazandaran University of Medical Sciences, 2020)
Context: Low birth weight infants are prone to an altered ocular development in childhood, resulting in refractive errors of the eye. Myopia (short-sightedness) is the most common refractive error of the eye that reduces vision. Evidence Acquisition: A PubMed literature search was conducted using the following search terms: "low birth weight infant", "myopia", "prematurity", and "refractive error". Results: The underlying cause of myopia is usually excessive growth of the eye, which is under the influence of early-life pressure on human growth. Children with low birth weight have significantly shallower anterior chamber depth and thicker lens. At the ages of 10-12 years, preterm children have an increased likelihood of all types of refractive errors. However, in low birth weight children, a 1 diopter of myopic change occurs over the first decade of life. Conclusions: The progression of myopia is higher in children with low birth weight, suggesting that prematurity and low birth weight may simultaneously affect the development of optical components, leading to myopia.